2020
DOI: 10.3389/frobt.2020.578805
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Survey of Telerobotic Time Delay Mitigation

Abstract: There is a substantial number of telerobotics and teleoperation applications ranging from space operations, ground/aerial robotics, drive-by-wire systems to medical interventions. Major obstacles for such applications include latency, channel corruptions, and bandwidth which limit teleoperation efficacy. This survey reviews the time delay problem in teleoperation systems. We briefly review different solutions from early approaches which consist of control-theory-based models and user interface designs and focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…A recent study in medical robotics reported that more than 0.4 s delay affected the surgeon's performance (Madder et al, 2020). Therefore, further study is required to confirm that our system works in high-latency networks and approaches to mitigate time delay should be considered (Farajiparvar et al, 2020).…”
Section: Limitationsmentioning
confidence: 91%
“…A recent study in medical robotics reported that more than 0.4 s delay affected the surgeon's performance (Madder et al, 2020). Therefore, further study is required to confirm that our system works in high-latency networks and approaches to mitigate time delay should be considered (Farajiparvar et al, 2020).…”
Section: Limitationsmentioning
confidence: 91%
“…For topics, we only consider multiplayer interactive systems, so this excludes the related area of tele-operation, which can also sufer from network latency. The interested reader is encouraged to refer to a survey by Farajiparvar et al [44] for more information on this topic.…”
Section: Methodology To Obtain Paper Poolmentioning
confidence: 99%
“…The increased distance between the components, as well as the fact that the infrastructure is shared with other (unknown) users, makes precise control over the timing more challenging. One way to compensate for this is to reduce the frequency of the cycle, provided that the controlled process allows for it, or to adopt predictive strategies [145] that attempt to estimate the state of the remote system and revise control commands accordingly.…”
Section: A Model For Networked Control Beyond Point-to-pointmentioning
confidence: 99%